(untitled) (Research, Society and Development, 2021)
Spinal cord injury occurs as a consequence of some trauma, altering the motor capacity and/or sensitivity (or both) of the entire body segment or part of it, thus affecting the quality of life of affected people. The aim of the study is to understand the main nursing care for people with spinal cord injury (SCI). This is an integrative literature review study, developed through attached articles in the nursing databases (BDENF) and Academic Google. Due to changes after spinal cord injury, the provision of adequate nursing care contributes to the promotion of well-being and prevents health problems. The results of the integrative review showed that the main nursing interventions for patients with spinal cord injury are related to care for pressure injuries, immobility, urinary retention, feelings of anxiety, feeding, self-care, constipation, risk of autonomic dysreflexia and dysreflexia autonomic. Therefore, it is essential that the nursing professional strives for this care to be performed correctly, aiming at the particularities and needs of each patient, so that they can contribute to facing limitations and improving biopsychosocial.